Capacity Building for Farming System Digitalization Using Farming Management System - Hidayat, Rahmat; Amnur, Hidra; Alanda, Alde; Yuhefizar; Satria, Deni (SOTVI, 2023)
Agriculture is one of the most important areas of human activity around the world. As the population increases, it is necessary to increase agricultural production. In the age of information technology, information plays a key role in people's lives. Agriculture is rapidly becoming a highly development-intensive industry where farmers need to collect and evaluate a large amount of information in their business processes to become more efficient in production and communicate information accordingly. Modernizing agriculture requires technological know-how for the efficient use of agricultural inputs. It deals with factors such as ecological footprint, product safety, labor welfare, nutritional responsibility, plant/animal health and welfare, economic responsibility and local market presence. They cover almost all stages in the production chain concerning day-to-day agricultural tasks, transactional activities for all stakeholders involved, and support for information transparency in the food chain. The use of information technology and network infrastructure currently enables the application of technology in agricultural business processes, but there is no standardized solution to enable interoperability and integration among services and stakeholders. Farming Management System (FMS) is expected to be a solution and standard in the use of technology in agriculture. Farming management system is a management system specifically designed to assist farmers or farm managers in managing their farming operations more efficiently and effectively. This system usually consists of integrated software and hardware to monitor and collect data from various aspects of agriculture, such as irrigation, fertilization, pesticide spraying, etc.